Nucleation mechanisms of iodic acid in clean and polluted coastal regions. (August 2020) - Rong, Hui; Liu, Jiarong; Zhang, Yujia; Du, Lin; Zhang, Xiuhui; Li, Zesheng
Abstract: In coastal regions, intense bursts of particles are frequently observed with high concentrations of iodine species, especially iodic acid (IA). However, the nucleation mechanisms of IA, especially in polluted environments with high concentrations of sulfuric acid (SA) and ammonia (A), remain to be fully established. By quantum chemical calculations and atmospheric cluster dynamics code (ACDC) simulations, the self-nucleation of IA in clean coastal regions and that influenced by SA and A in polluted coastal regions are investigated. The results indicate that IA can form stable clusters stabilized by halogen bonds and hydrogen bonds through sequential addition of IA, and the self-nucleation of IA can instantly produce large amounts of stable clusters when the concentration of IA is high during low tide, which is consistent with the observation that intense particle bursts were linked to high concentrations of IA in clean coastal regions. Besides, SA and A can stabilize IA clusters by the formation of more halogen bonds and hydrogen bonds as well as proton transfers, and the binary nucleation of IA-SA/A rather than the self-nucleation of IA appears to be the dominant pathways in polluted coastal regions, especially in winter. These new insights are helpful to understand the mechanisms of new particle formation induced by IA in clean and polluted coastal regions. Graphical abstract: Image 1 Highlights: Halogen and hydrogen bonds stabilize IA and IA-SA/A clusters. IA self-nucleation can initiate new particle bursts in clean coastal regions. In polluted coastal regions, IA-SA/A binary nucleation is predominant.